Praperadilan Sebagai Upaya Perlindungan Hak Asasi Tersangka dalam Proses Penyidikan - Anjas Manuturi Banjarnahor; Lesson Sihotang (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
The pretrial institution serves to regulate the use of coercive measures by authorized organizations during the investigation and prosecution stages. The establishment of this institution is a primary priority aimed at protecting the rights of suspects, particularly in cases involving unlawful arrest or detention, the termination of investigations and prosecutions, and other similar circumstances. However, several weaknesses remain in both the design and implementation of this institution within the judicial system, resulting in insufficient protection of human rights for suspects, despite its regulation under positive law, namely Law Number 8 of 1981. Efforts to safeguard the human rights of suspects during the investigation process constitute the main focus of this study, which examines the legal status of pretrial procedures within Indonesia’s criminal justice system, the challenges in their implementation as a means of protection, the effectiveness of pretrial rulings in this context, and their implications for subsequent investigations.